Test Platform Development for Fuel Cell Vehicle’s Hydrogen Management System - LAI Xunian; LI Ling; LIANG Weiming; WANG Binglong; LIU Fen (Institute of Advanced Engineering and Science, 2012)
This paper has proposed a Hardware-in-Loop test platform for Hydrogen Management System (Short for HMS) based on hardware of PXI and software of LabVIEW of National Instrument company(short for NI) and Matlab/Simulink for plug-in fuel cell vehicle, replacing the real car experiment platform with the feature of complicated test environment, variable parameter, and limited condition in debugging stage. According to HMS working behavior, it has designed the HMS model by simulink for the test platform. And according to HMS’s control strategy, I/O signal map, CAN communication and sensor characteristics, it has designed the platform hardware configuration, software program, test interface, and rapidly made validation to control logic and fault diagnosis of Hydrogen Management Unit (Short for HMU). The experiment result shows that this test platform is effective for HMU control logic validation, system status monitor, fault injection, fault tracing, and it can shorten the vehicle research and development cycle, reduce the development cost, optimize test environment and promise safety for test engineer. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1639